ANALISIS PERTIMBANGAN HAKIM JUDEX JURIST PADA PUTUSAN BEBAS DALAM TINDAK PIDANA PENCURIAN DENGAN KEKERASAN YANG MENGAKIBATKAN KEMATIAN - Yosef Firman Buulolo (Jurnal Panah Hukum, 2026)
Theft with violence that causes death is a criminal act that qualifies as taking property with violence, which is carried out with the aim of facilitating the action and resulting in serious injury or death to the victim. For punishment or sanctions in cases of crimes of theft with violence that cause death, this is regulated in Article 365 paragraph (4) of the Criminal Code. The perpetrator was threatened with the death penalty, life imprisonment or imprisonment for up to twenty years, but in the end the Supreme Court Judge decided to acquit him because the District Court and High Court Judges were not careful in giving their verdict. The investigative method applied by the author is normative legal investigation, which adopts a juridical approach, a casuistic approach and an analytical approach. Secondary data collection was carried out through a literature review consisting of primary legal material, secondary legal material and tertiary legal material. The data analysis used is descriptive qualitative data analysis, with conclusions drawn using deductive methods. Based on the findings of the investigation and discussion, it can be concluded that the application of the law in this decision was inappropriate, because the defendant was acquitted by the judge in Decision Number 429/K/PID/2017. According to the author, the defendant should be charged under Article 365 paragraph (4), because based on the chronology of events, witness statements, evidence, and the defendant's statement in this case have fulfilled the elements contained in the statutory regulations. The author suggests that the Panel of Judges who hear and decide a criminal case should be more thorough and accurate in determining the actions taken, so that they can be adjusted to the provisions contained in the statutory regulations.